Mindfulness in Teaching and Teacher Engagement: The Mediating Role of Teacher Resilience - Nurshadrina, Amanda; Septiana, Eva; Widyasari, Pratiwi (UI Scholars Hub, 2025)
Teaching requires the fulfillment of multiple roles, including enhancing instructional practices, fostering student learning, serving as a role model, and collaborating with colleagues while adapting to the new curriculum, Kurikulum Merdeka. Consequently, teacher engagement is essential for improving teacher performance. Engaged teachers also experience better well-being and are less likely to face mental health challenges. According to the Job-Demands Resource Model, mindfulness in teaching and teacher resilience can be regarded as personal resources that foster teacher engagement. This study aims to investigate the relationship between mindfulness in teaching, teacher resilience, and teacher engagement. A total of 417 Indonesian teachers participated in this study by completing the three standardized scales: Mindfulness in Teaching Scale, Multidimensional Teacher Resilience Scale, and Engaged Teacher Scale. The result indicates a significant positive relationship between mindfulness in teaching and teacher engagement, fully mediated by teacher resilience. Mindfulness in teaching enhanced teacher resilience, which, in turn, fostered teacher engagement. These findings highlight the crucial role of mindfulness in teaching as a personal resource that enables teachers to navigate challenges and maintain engagement through improved resilience. The study emphasizes the importance of incorporating mindfulness practices into teachers’ daily lives to support them in their multifaceted roles.